Kontribusi Kesejahteraan Masyarakat, Investasi dan Dampak Pandemi COVID-19 Terhadap Penyerapan Tenaga Kerja Generasi Z - Suryadi Suryadi (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2023)
Generation Z has different characteristics compared with other generations. They prefer technology, flexibility, and intelligence and are more tolerant of cultural diversity. This writing uses panel data to analyze the contribution of people's welfare, investment, and COVID-19 impact on Generation Z labor intake. The corresponding panel data model is the Random Effect Model. The study showed that the people welfare variable has a significant negative influence at the amount of 0.64 upon Generation Z labor intake. While investment has a significant positive effect of 0.71 and the variable of COVID-19 impact resulted in a negative of 0,002 however it is not considered a significant number.